Cannabinoid receptor 1 promotes M1 polarization of macrophages through the Gαi/o/RhoA signaling pathway in mice with acute lung injury - MA Xiuzhen; ZHOU Ni; GUO Siqi; WANG Yuanyuan; MAI Ping (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To explore the effects and potential molecular mechanisms of blocking cannabinoid receptor 1 (CB1) in acute lung injury (ALI) in mice.Methods·Forty mice were randomly divided into blank control group, AM281 (CB1 antagonist) control group, lipopolysaccharide (LPS) group, and LPS＋AM281 group, with ten mice in each group. ALI models were induced by LPS. The pathological manifestations of lung tissues were observed in each group of mice by hematoxylin and eosin (H-E) staining and the inflammation scores were calculated. The mRNA levels of M1 markers [tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), IL-12] and M2 markers [arginase (Arg), mannose receptor, C type 2 (Mrc2), macrophage galactose-type lectin 1 (Mgl1)] in lung macrophages were measured by reverse transcription and real-time fluorescence quantitative polymerase chain reaction (qPCR). Human myeloid leukemia monocytes THP-1 cells were cultured in vitro, and the expression of CB1 and CB2 in THP-1 cells was detected by immunofluorescence. After further blocking CB1 and inhibiting the Gαi/o/RhoA signaling pathway, the mRNA levels of M1 markers were assessed.Results·The LPS group showed significant lung tissue damage and a significant increase in inflammation scores in mice. After blocking CB1, compared with the LPS group, the LPS＋AM281 group of mice showed improvements in lung injury, manifested as improved congestion of alveolar wall capillaries, reduced infiltration of inflammatory cells in the lung interstitium and alveolar cavity, and a decreased inflammation score (P=0.007). Compared with the control group, the levels of M1 marker in the lung tissue of the LPS group were upregulated, while the polarization of macrophages changed and the M1/M2 ratio was reversed after blocking CB1 (all P<0.05). In vitro studies found that macrophages expressed CB1 and CB2. Activation of CB1 by arachidonyl-2-chloroethylamide (ACEA) upregulated the expression of M1 markers. Blocking CB1 and selectively inhibiting Gαi/o/RhoA signaling significantly downregulated M1 markers (all P<0.05).Conclusion·CB1 promotes the polarization of macrophage towards the M1 phenotype through the Gαi/o/RhoA signaling pathway in ALI, and blocking CB1 can improve lung injury.